Perbandingan Mutu Tepung Karagenan Hasil Ekstraksi Metode Pemanas Ohmic Dan Konvensional - Iswahyono Iswahyono; Siti Djamila; Amal Bahariawan; Meta Fitri Rizkiana (JOFE : Journal of Food Engineering, 2022)
The ohmic technology was applied for the carrageenan extraction process from seaweed (Eucheuma cattoni). The principle of ohmic technology is based on passing an electric current through seaweed and triggering its internal energy. The objectives of this study were to compare two different extraction methods using the ohmic and conventional heaters in terms of the quality of carrageen flour. This study were conducted by two different heating sources during the seaweed extraction process, i.e., ohmic heating and conventional heating from a gas stove. Each method was repeated three times. The extracted filtrates were dried, milled, and sieved using an 80-mesh sieve, then the quality of carrageenan flour was measured. Quality of extracted carrageenan flour using the ohmic and conventional heating methods are: 1) the extraction yield of 45%; 42%, 2) moisture content 10%; 18%, 3) white degree 77.63%; 74.27%, 4) viscosity 6.02 cp; 4.57 cp and 5) gel strength 174 gr / cm2: 159 gr / cm2. The result of statistical analysis between two methods with α 5% showed no significant difference in yield parameters however significantly different for water content, white degree, viscosity, and gel strength. The quality of extracted carrageenan flour of the ohmic heating method was better compared to the conventional heater.